International disputes must still be solved by political means - Clarke, Andrew Emerson (Kent Law Review, 2017)
This article considers the (in)ability of international law to ensure compliance from United Nations (UN) Member States, absent political influence. It examines whether concepts such as sovereign equality, normativity and concreteness give legal authority to international law, and further whether this ‘authority’ is respected by Member States and strictly enforced by UN governing bodies and international courts. The article explains that where sovereign rights or national interests collide the International Court of Justice (ICJ) is often unable to give a ruling or advisory opinion based solely on legal grounds and demonstrates that the contemporary international regime is incapable of removing politics from international legal proceedings. Furthermore, the article analyses the United Nations Security Council’s (UNSC) failure to enforce ICJ rulings against the US and the inability to prevent the US-led invasion of Iraq in 2003. With respect to the Iraq invasion, it highlights how this invasion occurred in the face of existing international norms and rules which purported to curb unauthorized use-of-force by UN Member States. The paper deduces that existing international rules and structures which seek to ignore state politics cannot settle contemporary international disputes.